Analisis pengaruh nilai ekspor dan investasi bagi pertumbuhan ekonomi Indonesia dalam perspektif syariah - Abdul Rozak; Minhajuddin Minhajuddin; Marsya Rhani Revalina (Kompartemen: Jurnal Ilmiah Akuntansi)
This research examines the impact of export value and investment on Indonesia's economic growth from 2013 to 2022 from an Islamic perspective. Using secondary data from the Central Bureau of Statistics and the World Bank, the Error Correction Model method is applied to analyze the long-term and short-term relationships between variables. Stationarity Test, R-Square Test, F Test, and T Test are used to ensure the model's validity. The research results show that export value and investment significantly affect long-term economic growth. In the short term, exports are significant at the 5 percent significance level, and investment is significant at the 10 percent significance level for economic growth. From the Islamic perspective, the economic growth resulting from increased exports and investment positively impacts the economic and social dynamics of society, ensuring a fair distribution of welfare. By applying Sharia principles, the benefits of economic growth can be felt evenly, avoiding unethical practices. Exports and investment are crucial factors in driving Indonesia's economic growth, while Sharia principles provide a strong foundation for economic justice and sustainability.